Promoting Higher-Order Thinking Skills (HOTS) for Young Learners in A Bilingual Classroom - Anang Widodo (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2022)
Adopting Bloom's Taxonomy of higher-order thinking skills (HOTS) in a bilingual classroom, especially for young learners, needs creativity and extra effort from teachers since it deals with involving students with complex activities and difficult tasks. This present study reveals how to implement HOTS in a bilingual classroom and the challenges during the learning-teaching activities. This study involved 21 second-grade students of Al – Azhar 55 Islamic Primary School in Yogyakarta, two homeroom teachers, and a native speaker. The data were collected from the interview, document analysis, and classroom observation. The result of the study shows that to promote HOTS during the learning-teaching activities, the teacher implements hands-on learning teaching strategies and involves ICT to help students understand the topic discussed easily in a fun way. Meanwhile, the challenges occurring lie in students' motivation to learn and lack of skill in writing. This study yields interesting results which can give another option to implement HOTS for young learners in the context of the bilingual classroom.